Nicorandil-induced penile ulcerations: A case report and review of the penile cutaneous circulation. (September 2016) - Jones, C.D.; Ng, M.; Ray, A.
Abstract: Mucosal and cutaneous ulceration as a result of nicorandil use is well described in the literature. Nicorandil induced penile ulceration is a rare clinical manifestation. Six cases arising from either the dorsal or lateral prepuce have been reported in current literature. We present a case of nicorandil induced penile ulceration affecting the dorsolateral prepuce and give an overview of the penile cutaneous circulation.